Corruption in health care: Victims of white coat crime in Serbia - Vasiljević-Prodanović Danica (Temida)
The subject of this paper is corruption in health care, with particular focus on some forms of corruption that occur in direct interaction between doctor and patient. These forms of corruption, conditionally called minor corruption, are usually included within the criminal offenses of bribery and abuse of official duty. The law stipulates that both offering and accepting a bribe are criminal offenses. The question that arises is who are the victims and who the perpetrators of “white coat” crime? The aim of this paper is to consider the phenomenological characteristics and mechanisms of minor corruption in health care. This paper presents the results of the exploratory study conducted in five medical institutions in Belgrade, during July 2014, on a convenient sample of health workers who were willing to speak about this sensitive topic. [Projekat Ministarstva nauke Republike Srbije, br. 179044: Razvoj metodologije evidentiranja kriminaliteta kao osnova efikasnih mera za njegovo suzbijanje i prevenciju]